Meningkatkan Hasil Belajar Peserta Didik dengan Menggunakan Model Pembelajaran PjBL Pada Pembelajaran IPAS di Kelas V SD Negeri 107417 Sei Merah - Maifah Hanim Br Panjaitan; Dalimawaty Kadir; Nurhafni Siregar; Fitriani Fitriani; Reni Agustina Simanjuntak (Journal on Education, 2024)
This research was conducted based on observations that found that class V students did not have interest and motivation in participating in the learning process. The aim is to evaluate student learning outcomes using the project based learning model, as part of efforts to improve the quality of learning in class using the PTK method. This research was conducted at SD Negeri 107417 Sei Merah in April-May 2024, with research subjects being class V students with a total of 22 students. The research results show an increase in student learning outcomes in science subjects on topic A, how breathing can help you carry out daily activities. In cycle I, the percentage of learning outcomes for class V students at SDN 107417 Sei Merah increased from the percentage of student learning outcomes at the time of observation, namely increasing from 27.27% at the time of observation to 50% at the end of cycle I and in cycle II the percentage of student learning outcomes. class V SDN 107417 Sei Merah increased significantly. The percentage of student learning outcomes during observation was only 27.27%, increasing to 86.36% at the end of cycle II.